1989
DOI: 10.1002/bip.360280120
|View full text |Cite
|
Sign up to set email alerts
|

Conformationally constrained D,L‐alternating oligopeptides

Abstract: The possibility of selectively reducing the number of beta-helical structures theoretically possible for a D,L-alternating peptide by using a N-methyl group as conformational constraint is considered. Some 1H-nmr data regarding Boc(L-Nle-D-Nle)3-L-Nle-D-MeNle-L-Nle-D-Nle-L-Nle-OMe (I), its formyl analogue (II), and the pentadecapeptide Boc(D-Leu-L-Leu)5-D-MeLeu-(L-Leu-D-Leu)2-OMe (III) are presented. It is shown that these alternating stereocooligopeptides with a N-methyl group in the (n - 3) (I and II) or (n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

1993
1993
2010
2010

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…There has been established a direct correlation between the participation of an NH group in a H bond and its δ NH for oligopeptides in nonpolar solvents 11. The δ NH > 7.0 ppm for those NH groups implied in H bond, whereas for those not involved in H‐bond δ NH the values are between 6.5 and 7.0 ppm.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There has been established a direct correlation between the participation of an NH group in a H bond and its δ NH for oligopeptides in nonpolar solvents 11. The δ NH > 7.0 ppm for those NH groups implied in H bond, whereas for those not involved in H‐bond δ NH the values are between 6.5 and 7.0 ppm.…”
Section: Discussionmentioning
confidence: 99%
“…Several D,L ‐alternating oligonorleucine have been synthesized for the characterization of these structures and to study the contribution of hydrophobic interaction of the linear side chains that stabilize one specific helical conformation. In attempts to achieve specific kinds of β‐helices by using the N‐methyl group as conformational constraint, a set of D,L ‐alternating oligonorleucines having a N‐methylated residue at the fourth‐last position of the chain10, 11 were synthesized and investigated.…”
Section: Introductionmentioning
confidence: 99%
“…There has been established a direct correlation between the participation of an NH group in a H bond and its ␦ NH for oligopeptides in nonpolar solvents. 11 The ␦ NH Ͼ 7.0 ppm for those NH groups implied in H bond, whereas for those not involved in H-bond ␦ NH the values are between 6.5 and 7.0 ppm. From the Table I it can be observed that the residues with ␦ NH Ͼ 7.0 ppm are 3, 5, 6, 7, 8, 10, and 12, whereas those with ␦ NH between 6.5 and 7.0 ppm are 2, 4, and 11.…”
Section: Discussionmentioning
confidence: 99%
“…the backbone torsion angles of every second amino acid agree. It was very interesting to see two alternating L , D ‐polypeptide strands forming double helices as an alternative to the single‐stranded helices (Figure 1b and c)8–19.…”
Section: Introductionmentioning
confidence: 99%